Azble (coffee table) / Muhammad Azharuddin Zakaria - Zakaria, Muhammad Azharuddin (Faculty of Applied Sciences, 2017)
Shortage of material supply for furniture production is one the reason why wooden pallet is one of the alternatives to replace hardwood materials in making furniture. In this study, the Azble (Coffee Table) was designed and produced by using wooden pallet (pine species) and combination of bamboo for' the appearance enhancement. After Azble (Coffee Table) has been produced, the survey was done by randomly distributing a set of questionnaires to 139 correspondents in UiTM Jengka and Bandar Pusat Jengka, Pahang. There were a few issues have been analyzed such as raw material, design and marketing. Based on the results, most of correspondents of each factors agreed that these kinds of issues such as suitability of raw material, people devoted to wooden furniture, wooden pallet is cheap and easy to get, combination of wooden pallet with bamboo, color, following the trend, concept of green design and modern concept, suitability for indoor furniture, designated for living room, space and commercialized in the market meet the customer's satisfaction.